An electrodeposited Au nanoparticle/porous graphene nanoribbon composite for electrochemical detection of alpha-fetoprotein - Jothi, Lavanya; Jaganathan, Saravana Kumar; Nageswaran, Gomathi (Materials chemistry and physics, 2020)
In this work, a novel label-free electrochemical immunosensor for the detection of alpha-fetoprotein (AFP) is fabricated for early diagnosis and prognostics of liver cancer. A porous graphene nanoribbon (PGNR) was synthesized via chemical reduction method and it was electrodeposited with gold nanoparticles (AuNPs) to obtain AuNPs/PGNR hybrid nanomaterial. Anti-AFP was immobilized onto AuNPs/PGNR/glassy carbon electrode and anti-AFP/AuNPs/PGNR/GCE was further studied to demonstrate its electrocatalytic activity towards AFP antigen. PGNR enhances the electroactive surface area and the electron transfer ability between the electrode and redox probe while the AuNPs deposited on PGNR are used to immobilize biomolecules and to facilitate the electron transport. The superior biosensing performance towards AFP under physiological pH condition is demonstrated by a corresponding decreased peak current in differential pulse voltammetry for a wide linear range (5–60 ng/mL) with a low detection limit of 1 ng/mL. Detection of AFP in serum samples by this label-free electrochemical immunosensor without fouling or significant interference implies that the anti-AFP/AuNPs/PGNR modified GCE has a great application potential for clinical diagnosis of AFP. [Display omitted] •A novel porous graphene nanoribbon was obtained via chemical reduction method.•AuNPs electrodeposited on porous graphene nanoribbon acts as platform for immobilizing biomolecule.•Porous graphene nanoribbon/AuNPs can be used for detection of AFP in human serum.